Regulation of PP2A by Sphingolipid Metabolism and Signaling - Oaks, Joshua (Front Oncol, 2015)
Protein phosphatase 2A (PP2A) is a serine/threonine phosphatase that is a primary regulator of cellular proliferation through targeting of proliferative kinases, cell cycle regulators, and apoptosis inhibitors. It is through the regulation of these regulatory elements that gives PP2A tumor suppressor functions. In addition to mutations on the regulatory subunits, the phosphatase/tumor suppressing activity of PP2A is also inhibited in several cancer types due to overexpression or modification of the endogenous PP2A inhibitors such as SET/I2PP2A. This review focuses on the current literature regarding the interactions between the lipid signaling molecules, selectively sphingolipids, and the PP2A inhibitor SET for the regulation of PP2A, and the therapeutic potential of sphingolipids as PP2A activators for tumor suppression via targeting SET oncoprotein.